The judiciary and the bar (Syariah) - Ali Mohamed, Ashgar Ali; Ali Tajuddin, Hanifah Haydar (CLJ Publication, 2020)
Based on the above, this chapter will focus inter alia, on the Syariah judiciary, the appointment of members of prosecution and representation11 and the qualifications to be a Syarie lawyers.